Analisis Usability dalam User Experience pada Sistem KRS Online UMM menggunakan USE Questionnaire - Wahyu Andhyka Kusuma; Vebrian Noviasari; Gita Indah Marthasari (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
KRS-Online system is a web-based information system to assist the process of preparing the KRS of every student in University of Muhammadiyah Malang. In this research, the level of usability of the system will be measured and the relationship between the independent variables (usefulness,ease of use, and ease of learning) and dependent variable (satisfaction), either simultaneously or partially, will be analyzed. Usability measurement adopted in this study is USE questionnaire that contains usefulness, ease of use, ease of learning, and satisfaction variables. This research involves 100 respondents from the KRS-Online system users. The result shows that measuring usability produces feasibility of 73.312%, which means usability of KRS-Online system is "acceptable". On the other hand, this study proves that there is a significant influence between usefulness, ease of use, and ease of learning variables with the satisfaction variable simultaneously. In addition, usefulness and ease of use variables significantly affect the satisfaction variable partially, while the ease of learning variable does not significantly affect the satisfaction variable.